2020
DOI: 10.1111/1747-0080.12612
|View full text |Cite
|
Sign up to set email alerts
|

Limited dietary interventions in rural Australian communities: A systematic review

Abstract: Aim This review aimed to synthesise the evidence on the effectiveness of dietary interventions targeting adolescents (>13 years) and adults living in rural or remote Australia. Methods Six electronic databases were searched to identify dietary interventions undertaken in rural or remote communities. Studies were included if they utilised intervention and control comparisons or pre and post assessment of diet‐related outcomes. If studies included metropolitan populations, dietary outcome measures had to be prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…In 2018, 38% of the burden of disease in Australia was attributed to modifiable risk factors, with dietary risk factors directly accounting for 5.4% of the total burden of disease [2]. Worldwide, specific dietary risk factors for the development of diet-related disease have been identified as low consumption of fruits, vegetables and wholegrains, together with rising consumption of sodium and saturated fats [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, 38% of the burden of disease in Australia was attributed to modifiable risk factors, with dietary risk factors directly accounting for 5.4% of the total burden of disease [2]. Worldwide, specific dietary risk factors for the development of diet-related disease have been identified as low consumption of fruits, vegetables and wholegrains, together with rising consumption of sodium and saturated fats [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…There is limited Australian evaluation of nutrition education programs focusing on food literacy, especially in regional Australian communities [11]. Only two programs, primarily focused on cooking skills, have shown positive dietary and social behaviours in the regional Australian context.…”
Section: Introductionmentioning
confidence: 99%
“…This study identified the lack of dietary data collected from rural areas as a major barrier preventing further modelling in all rural and remote areas of Australia. Additionally, a recent review by Alston & Partridge identified a lack of evidence from intervention studies that aimed to improve dietary intake in rural Australia over the past 20 years and a major limiting factor was that dietitians and/or nutritionists were rarely involved in study design or delivery [ 9 ]. Given there is a lack of high level investment and progress made in addressing issues with healthcare access in rural and remote areas of Australia, interventions to reduce dietary risk factors are important to support the health of current and future generations.…”
Section: Introductionmentioning
confidence: 99%